THE FRONTIER OF THE MODERN AND THE FUTURE: THE MOVEMENT OF THE POSSIBLE AND THE WORTHY - Shedyakov, Vladimir (Collection of scientific papers «ΛΌГOΣ», 2025)
It is well known that the understanding of “frontier” (as opposed to, for example, the border) is not only a territory of meeting of cultural-civilizational worlds, but also the interpenetration of different perceptions and understandings, the originality of forms and practices of cultures, economic management, the uniqueness of history, social experience and mental codes. The history of science and practice has shown that the evolution of the term “frontier” allows it to be fruitfully used in the process of studying the relationship of both cross-cultural characteristics and the specificity of cultural-civilizational worlds, shading the paths of formation and the diversity of the result of the socio-cultural landscape, the perception and organization of reality and space [1-5]. Even such signs of the times of the classical frontier appear, as, for example, a network of trading posts – points of development within uncontrolled territories. The ability to move forward without suppressing originality, but involving in the culture of development, is now worthy and objectively required.